The Effect Of Brainstorming Group On Breast Cancer Prevention In Adolescents - Rotua Suriany Simamora; Putri Lestari (UrbanGreen, 2020)
Breast cancer is a type of malignant disease that is greatly feared by women. Breast cancer is the second highest cancer incidence in the world that most often affects women. The high incidence of breast cancer need to be observed by prevention and early detection. Health education is one method to increase knowledge about breast cancer. Health education will be conducted by researchers in the prevention of breast cancer is with a group brainstorming method. This study is a Quasi Experiment, or who have a treatment by using pre-test and post test without control group. The study population was a teenager using a sampling that is purposive sampling. The results using Paired T-Test prior to the brainstorming group mean value of 2.08, after doing the brainstorming group mean value of 1.33, and p value of 0.000 (p value> 0.05). It can be concluded that there is a difference in the prevention of breast cancer before and after brainstorming group in adolescents